Iceland’s External Affairs from 1400 to the Reformation: Anglo-German Economic and Societal Shelter in a Danish Political Vacuum - Þórhallsson, Baldur; Kristinsson, Þorsteinn (Stjórnsýslustofnun, 2013)
The paper applies the assumption that small states/entities need economic and political shelter in order to prosper, to the case of Iceland in the period from 1400 to the Reformation in the mid-16th century. Also, it applies the findings from the first paper in this ‘hexalogy’ (a six-paper series) on Iceland’s external relations in a historical context, i.e. that Iceland enjoyed societal shelter in the Middle Ages, to this period. The aim is both to analyse whether or not Icelanders enjoyed economic, political and societal cover from their engagements with the Danes, English and Germans and to evaluate the validity of the ‘shelter theory’. The paper argues that Iceland enjoyed considerable economic and societal shelter from its encounters with English and German merchants and fishermen in a period in which Danish political cover was formally in place but was not effective in practice. Moreover, the paper claims that the shelter theory, and small-state studies in general, need to take notice of the importance of social communication with the outside world for a small entity/state. Also, the Danish political vacuum in our late Medieval Period provided the islanders with economic opportunities and social engagements with the wider world. This was at the cost of continued domestic clashes between the islanders themselves, on the one hand, and between them and ‘outsiders’ on the other. Our findings indicate that in the case of Iceland there might be a trade-off between the benefits of strict political cover by a single external actor, and the economic and societal opportunities accompanied by a lack of political affiliations.